Analysis of coir based fibre/epoxy composites plate subject to aeroelastic instability - Abdul Rahman, Mohd Amirul (2014)
The effects of aspect ratio and fiber-epoxy weight ratio of coir fibre/epoxy composite wing idealized as flat plate on flutter speed were preliminary studied in the current research to investigate the aeroelastic instability on natural fiber composite material. Among the main concerns of composite materials application for aircraft are weight saving and cost reduction factor while the design of structures should be made stiffer to avoid aeroelastic instability problems. In connection between aeroelasticity and environmental issue, the usage of natural material like coir fiber reinforce composite might turn up as potential solutions for the problem of increasing aircraft weight & cost in making airframe more rigid with the purpose of reducing aeroelastic instability in addition of utilization of eco-friendly factor material. The coir fiber reinforces offer low in weight and cost reduction, and is more environmentally friendly compared to metallic materials. For the current work, the analysis of the coir fiber on the aeroelastic problem will be preliminary investigated to establish related data to be served especially in the aerospace research areas. Several previous researches that introduced the natural fibres to optimize the performance of structure have been done generally in other mechanical and civil research areas while conventional glass or carbon fibre reinforced composites has been traditionally used in the aeroelastic research. The research began with the existing raw untreated coir fibre which in the form of pressed mat and originally in random oriented fibre form are used in the composite preparation process by simple handlay-up and compression moulding method under room temperature and controlled pressure conditions. Then, the fabricated panels underwent material mechanical tests; tensile, flexural, and torsion test to obtain material mechanical properties. The 25% wt fiber composite has been selected as the highest performance specimen among others. The specimen with different aspect ratios (AR5, AR6, and AR7) with 25% wt fiber reinforcement composite underwent modal testing to get the mode shapes, natural frequencies, and damping ratios. The result shows that the plates with higher aspect ratio seem to have higher natural frequency and damping ratio. Then, the specimens of different aspect ratio (6 and 7) were installed in the wind tunnel for subsonic experimental aeroelastic test. The result shows that the plates with lower aspect ratio seem to have higher flutter speed. In terms of aeroelastic point of view, the results shows that there is a potential in the use coir fibers for secondary aircraft structures due to low density and vibration damping characteristics, in addition to low cost and green technology considerations. The preliminary data established potentially serve as a reference for future studies.